1992
DOI: 10.1128/aac.36.9.1817
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequences of CAZ-2, CAZ-6, and CAZ-7 beta-lactamase genes

Abstract: CAZ-2, CAZ-6, and CAZ-7 are plasmid-mediated P-lactamases that are markedly active against ceftazidime. The corresponding structural genes were amplified by the polymerase chain reaction. Nucleotide sequences were determined by direct sequencing of the amplified products. Analysis of the nucleotide and the deduced amino acid sequences showed that CAZ-2, CAZ-6, and CAZ-7 are derived from TEM-2 by three, four, and two amino acid substitutions, respectively. All these substitutions are located at positions 102, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 11 publications
(8 reference statements)
1
32
0
Order By: Relevance
“…Nucleotide sequence analysis showed that it differed from the TEM-2 sequence by four substitutions leading to the amino acid replacements Glu3Lys-104, Arg3Ser-164, Ala3Thr-237, and Glu3Lys-239 (positions are numbered in accordance with the system of Ambler et al [3]) and by one silent mutation at position 925 (A3G) (according to Sutcliffe's numbering system [41]). These substitutions are identical to those previously described for TEM-24, except for the cytidine at position 682, which is identical to the bla TEM-2 gene, instead of the silent mutation (C3T) as described previously (10).…”
Section: Resultsmentioning
confidence: 58%
“…Nucleotide sequence analysis showed that it differed from the TEM-2 sequence by four substitutions leading to the amino acid replacements Glu3Lys-104, Arg3Ser-164, Ala3Thr-237, and Glu3Lys-239 (positions are numbered in accordance with the system of Ambler et al [3]) and by one silent mutation at position 925 (A3G) (according to Sutcliffe's numbering system [41]). These substitutions are identical to those previously described for TEM-24, except for the cytidine at position 682, which is identical to the bla TEM-2 gene, instead of the silent mutation (C3T) as described previously (10).…”
Section: Resultsmentioning
confidence: 58%
“…The change Arg-1643Ser has been found previously in TEM-5, TEM-7, TEM-8, TEM-9, TEM-10, TEM-12, TEM-24, and TEM-26 (6,11,19). Dramatic changes in the hydrolysis of ceftazidime and aztreonam occurred when we introduced the mutation Ser-164.…”
Section: Discussionmentioning
confidence: 82%
“…In our work, the strains harboring such mutations required higher MICs of ceftazidime and aztreonam. The Ala-2373Thr change, found in TEM-5 and TEM-24 (6,29), is apparently neutral in relation to the tested antibiotics except for amoxicillin, which had a decreased MIC. This decrease of activity for penicillins has been shown previously by Healey et al (10).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…PCR was performed on plasmids extracted from the transconjugants and from the non-ESBLproducing P. mirabilis strain which was resistant to imipenem with primers J (forward, 5Ј-CTTATTCCCTTTTTTGCGGC-3Ј) and E (reverse, 5Ј-GGTCTGACAGTTACCAATGC-3Ј) (8) at positions 236 and 1079 of the TEM family gene ␤-lactamase according to Sutcliffe numbering (25). The sequence of the gene encoding the ␤-lactamase with a pI of 5.4 produced by the P. mirabilis strain was identical to that of TEM-1b (16,25), and the sequence of the gene encoding the ␤-lactamase with a pI of 6.5 was identical to that of the extended-broad-spectrum ␤-lactamase TEM-24b (8,17).…”
mentioning
confidence: 81%